Religiosity and Quality of Life in Older Christian Women in Ireland: A Mixed Methods Analysis. - Mc Garrigle, Christine; Kenny, Rose (My University, 2022)
This study used a mixed methods approach to understand the ways in which religion and quality of life (QoL) are associated in later life in Ireland. Longitudinal quantitative data from 2112 Christian women aged 57 and over at baseline (2009–10) participating in the Irish Longitudinal Study on Ageing (TILDA), as well as qualitative data from semi-structured interviews from 11 Christian women aged 65 and over in 2018, were used. The quantitative data showed an association between lower religiosity and lower QoL. Qualitative data supported an effect of religious involvement on QoL although certain aspects of being religious in Ireland were accompanied by distress. The data suggested that the relationship between religious attendance and higher QoL could be driven by multifactorial pathways, including psychological, social, and practical benefits.
PUBLISHED
Keywords: Ageing, Quality of life, Religion, Mixed methods; Ageing